1999
DOI: 10.1086/302507
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genetic Analyses Suggest Selection against Maternal Lineages in Bipolar Affective Disorder

Abstract: Previous reports of preferential transmission of bipolar affective disorder (BP) from the maternal versus the paternal lines in families suggested that this disorder may be caused by mitochondrial DNA mutations. We have sequenced the mitochondrial genome in 25 BP patients with family histories of psychiatric disorder that suggest matrilineal inheritance. No polymorphism identified more than once in this sequencing showed any significant association with BP in association studies using 94 cases and 94 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…In this respect, we also found two other missense variants that had previously been described as polymorhisms in patients with bipolar disorder. 25 These were the MTND5 C12403T (Leu23Phe) and MTND5 A12950C (Asn105Thr), and they were identified in two out of 23 and 24 bipolar patients, respectively. However, they were not found in QJ;a subsequent analysis of 94 control individuals.…”
Section: Discussionmentioning
confidence: 98%
“…In this respect, we also found two other missense variants that had previously been described as polymorhisms in patients with bipolar disorder. 25 These were the MTND5 C12403T (Leu23Phe) and MTND5 A12950C (Asn105Thr), and they were identified in two out of 23 and 24 bipolar patients, respectively. However, they were not found in QJ;a subsequent analysis of 94 control individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Two subjects shared 25 polymorphisms and these subjects belonged to the sub-haplogroup F1ba of the macro-haplogroup N, leading the authors to speculate that this haplotype may be a risk factor for atypical psychosis. However, Kirk et al (1999) resequenced the mitochondrial genome from 25 subjects with bipolar affective disorder who had family histories suggestive of inheritance from the maternal side, but they did not find a relationship between haplotype frequency in subjects with bipolar affective disorder compared to controls (85).…”
Section: Common and Novel Mitochondrial Dna Snps Associated With Psycmentioning
confidence: 97%
“…Kirk et al 116 sequenced the whole mitochondrial genome in 25 patients with bipolar disorder and demonstrated differences in the mitochondrial genetic distances within the bipolar and control groups. They determined these by making all the pairwise comparisons possible of mtDNA haplotypes in the bipolar or control groups and found that the bipolar group had fewer closely related haplotypes than controls, suggesting selection against certain haplotypes in the bipolar cases.…”
Section: Mood Disordersmentioning
confidence: 99%